Perancangan dan Pemanfaatan Limbah Oli Bekas Sebagai Sumber Alternatif pada Kompor - Cahyani, Renita; Meysila, Adisti; Purnomo, Danny; Libun, Jerry Moses; Huda, Rizal; Ambado, Gafur; Panjili, Moh Rafli (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The energy crisis and increasing environmental pollution due to used oil waste encourage the need to develop innovative alternative energy, especially in remote areas where it is difficult to access conventional fuel. This research aims to design a stove fueled by used oil as an alternative energy source that is environmentally friendly and economical. The stove design was carried out using AutoCAD software with a Design for Assembly (DFA) approach to produce a design that was efficient and easy to assemble. Test results show that the stove is capable of reaching combustion temperatures between 570–600°C with an average thermal efficiency of 5.1%. From an economic aspect, using this stove can save household energy costs by up to 30% with relatively low production costs. Apart from that, using used oil as fuel can reduce CO₂ emissions by up to 90% and reduce the potential for environmental pollution. A case study in Kiloma Village, Banggai Regency, Central Sulawesi, shows that this technology can be accepted and used effectively by the community.